JACK trial protocol: a phase III multicentre cluster randomised controlled trial of a school-based relationship and sexuality education intervention focusing on young male perspectives. Issue 7 (28th July 2018) - Lohan, Maria; Aventin, Áine; Clarke, Mike; Curran, Rhonda M; Maguire, Lisa; Hunter, Rachael; McDowell, Clíona; McDaid, Lisa; Young, Honor; White, James; Fletcher, Adam; French, Rebecca; et al.
Abstract : Introduction: Teenage pregnancy remains a worldwide health concern which is an outcome of, and contributor to, health inequalities. The need for gender-aware interventions with a focus on males in addressing teenage pregnancy has been highlighted as a global health need by WHO and identified in systematic reviews of (relationship and sexuality education (RSE)). This study aims to test the effectiveness of an interactive film-based RSE intervention, which draws explicit attention to the role of males in preventing an unintended pregnancy by reducing unprotected heterosexual teenage sex among males and females under age 16 years. Methods and analysis: A phase III cluster randomised trial with embedded process and economic evaluations. If I Were Jack encompasses a culturally sensitive interactive film, classroom materials, a teacher-trainer session and parent animations and will be delivered to replace some of the usual RSE for the target age group in schools in the intervention group. Schools in the control group will not receive the intervention and will continue with usual RSE. Participants will not be blinded to allocation. Schools are the unit of randomisation stratified per country and socioeconomic status. We aim to recruit 66 UK schools (24 in Northern Ireland; 14 in each of England, Scotland and Wales), including approximately 7900 pupils. A questionnaire will be administered at baseline and at 12–14 months postintervention. The primary outcome is reported unprotected sex, a surrogate measure associated with unintended teenage pregnancy. Secondary outcomes include knowledge, attitudes, skills and intentions relating to avoiding teenage pregnancy in addition to frequency of engagement in sexual intercourse, contraception use and diagnosis of sexually transmitted infections. Ethics and dissemination: Ethical approval was obtained from Queen's University Belfast. Results will be published in peer-reviewed journals and disseminated to stakeholders. Funding is from the National Institute for Health Research. Trial registration number: ISRCTN99459996